Impact of mass pheromone trapping on red palm weevil: adult population and infestation level in date palm gardens of Saudi Arabia - Vidyasagar , P . S . P . V . (2013)
The red palm weevil, Rhyncophorus ferrugineus Oliv. is a serious pest of date palm in all the Gulf countries. One of the important components of integrated management of the pest is the use of pheromone-based trapping system. After standardising the method of trapping with aggregation pheromone, 4-methyl-5-nonanol (Ferrolure) and/or 4-methyl-5-nonanol + 4-methyl-5-nonanone (9:1) (Ferrolure+), mass-trapping system was adopted for the entire Qatif region in the Eastern Province of Saudi Arabia. A total of 2252 pheromone traps were used in the mass trapping system. From an initial capital level of 4.12 weevils per trap per week in 1994, the adult population was reduced to 2.02 weevils per trap per week at the end of 1997. A grand total of 794657 weevils were trapped since the inception of the mass-trapping programme.The peak adult population trapped was immediately after winter season during the months of April and May. A much smaller second peak was observed during October and November months just before the onset of winter. When the weather parameters were correlated with the weevil catch in different months, it was found that there was a drop in capture rate of weevils at the beginning of winter season. After the integration of mass pheromone trapping-system into the control programme, there was a significant reduction in the infestation level of the pest.